Implementing Bruner's Theory for the Conceptual Understanding of Addition and Subtraction - Budiman, Pramesti Mayaza; Trimurtini, Trimurtini; Purwati, Panca Dewi (Faculty of Education Universitas Negeri Malang, 2023)
This research intends to describe the ability of first-year students to understand numbers and to explain their thinking processes in the arithmetic operations of addition and subtraction studied in Bruner's theory. Under the qualitative method with descriptive research design, this research was carried out during the 2nd batch of the Kampus Mengajar program, which the researcher joined. The research subjects were first-grade students at SD Sumogawe 04. The data were collected through several techniques, including observation, interviews, and documentation. The results indicated different understanding levels of the students. Once a student gets the number conservation laws, s/he is ready to learn the concept of numbers and their operations. The arithmetic operations taught to grade I students are addition and subtraction. Applying Bruner's learning theory could improve the quality of learning the target theme and stimulate the students' active participation in classroom activities which simultaneously led them to conceptual discovery.